1989
DOI: 10.1152/ajpgi.1989.256.6.g975
|View full text |Cite
|
Sign up to set email alerts
|

Gastric acid secretion and parietal cell mass: effects of thyroidectomy and thyroxine

Abstract: The role of thyroid hormones on parietal cell function and number was studied in the rat. Chronic administration of thyroxine (6-8 micrograms/100 g body wt/day) for 35 days significantly increased parietal cell mass (from 21.18 +/- 0.13 x 10(6) to 26.71 +/- 0.14 x 10(6] as well as basal acid secretion (from 3.69 +/- 0.08 to 4.99 +/- 0.16 mueq/10 min) and histamine-stimulated acid secretion (from 2.45 +/- 0.12 to 3.69 +/- 0.21 mueq/10 min). Thyroidectomy decreased the number of parietal cells in the gastric muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
1
8
0
1
Order By: Relevance
“…The reports that depletion of thyroid hormones inhibits the secretory functions of the digestive tract are fairly concordant [22, 23]. Hypothyroidism affects the entire gastrointestinal system and causes hypomotility [1, 7, 15].…”
Section: Discussionmentioning
confidence: 99%
“…The reports that depletion of thyroid hormones inhibits the secretory functions of the digestive tract are fairly concordant [22, 23]. Hypothyroidism affects the entire gastrointestinal system and causes hypomotility [1, 7, 15].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term T4 administration increased the mitotic activity of the fundic 'stem' cells of the stomach and basal and secretagogue-stimulated acid secretion via its effect on parietal cell mass (Adeniyi & Olowookorun, 1989). We recently found that prolonged administration of T4 significantly increased the incidence of rat colon tumours induced by azoxymethane (Iishi et al, 1992).…”
mentioning
confidence: 99%
“…Akiyama et al (1982) found out that the administration of thyroxine into rats led to significant increases in serum T 3 level, gastric pH (reduced acid secretion) and serum gastrin level. Adeniyi and Olowookorun observed that chronic administration of thyroxine increased parietal cell mass, as well as basal acid secretion and histamine-stimulated acid secretion (Adeniyi and Olowookorun, 1989), mice also show the same trend (Olaleye and Elegbe, 2005).…”
Section: Introductionmentioning
confidence: 82%